SYSTEMS AND METHODS OF MONITORING ELECTRODERMAL ACTIVITY (EDA) USING AN AC SIGNAL AND DISCRETE FOURIER TRANSFORM (DFT) ANALYSIS (2016)
Systems and methods of monitoring electrodermal activity (EDA) in human subjects suitable for use in wearable electronic devices. An EDA monitoring system can include first and second dry electrodes, an alternating current (AC) excitation signal source, a trans-impedance amplifier, an analog-to-digital (A-to-D) converter, a discrete Fourier transform (DFT) processor, and a microprocessor. The AC excitation signal source can produce an AC excitation signal having a predetermined excitation frequency, such as about 100 or 120 Hertz (Hz). The analog-to-digital (A-to-D) converter can include a sample-and-hold circuit that operates at a predetermined sampling frequency, such as about four times (4×) the predetermined excitation frequency of 100 or 120 Hz. The DFT processor can generate complex frequency domain representations of digitized, sampled voltage level sequences provided by the A-to-D converter for use in obtaining measures of a user's skin impedance or skin conductance.